SELF-SELECTED READING ACTIVITIES BY LEARNING STYLE PREFERENCES:PROMOTING READING TASK ENGAGEMENT IN TERTIARY CLASSROOM - Sari, Florita Diana (2013)
A number of studies suggest that allowing students to self-select reading material helps students become more willingreaders and increase the likelihood for deeper reading. However, it is not common for some English reading classes to allow students choosing reading materials, as they are usually prescribed by teacher or textbook (Zulfikar, 2009; Yembise, 2010). Recognizing choice as a well-known method for enhancing motivation, the current study employed students' choice to self-select reading activities as a techique to promotereading task engagement. This study aimed at investigating(i) students' self-selection of reading activities with regard to their learning style, and (ii) their engagement in doing the selected reading activities. Three reading materials from a compulsory textbook were differentiated into 12 reading activities, each responding to different combinations of learning style previously identified using ILS (Index of Learning Style). A sample of 54 students from one polytecnics school in Bandung self-selected the reading activities that they thought most pertinent to them. This study looked for their affective, behavioral, and cognitive engagements. Compatibility and incompatibility of students self-selection relative to their identified learning style was also examined to see any difference in reading task engagement. The ILS survey showed a majority of active (80.2%), sensor (83.1%), visual (81.7%), and sequential learners (81.7%). From self-reports, this evaluative case-study revealed six themes related to affective-behavioral-cognitive engagement, i.e. interest, imagination, challenge, relatedness, perceived compatibility, and external regulation. All responses combined, cognitive engagement (40.3%), affective engagement (39.7%), and behavioral engagement (14.0%) were recognized, with 6% of disaffection, orthe opposite of engagement. Participants with weak compatible self-selection (18.5%) were more likely engaged in the cognitive areas with less or no affective engagement. On the other hand, participants who made strong compatible self-selection (31.5%) were engaged more on the affective and behavioral aspects but at greater risk of disaffection due to unmet expectation on the reading activities they had chosen. The remaining 50% of participants, who made moderately compatible self-selection, were found to be engaged more on the cognitive area especially when they made intentional self-selection to activities that mismatched, either partially or fully, with their learning style. Readiness or internal regulation to self-select reading activities that were different from their usual expectation was one of the key factors in engaging students regardless of their learning style. Keywords: self-selection, learning style, differentiated activities, engagement